The Social Dynamics of The Batak Angkola Traditional Communities - Fitri, Hadiani; Suryana, Nina (Universitas Negeri Medan, 2022)
This paper examines how the process of social dynamics of the Angkola Batak takes place. There is a need for the Angkola Batak community to be able to understand the ins and outs of his family tree properly and correctly, by seeking identity their baldness which will later become the history of life. As we see a lot of today's society The Angkola Batak are again concerned about their ancestors, not just looking for grave land, instead find out about their tarombo and then form a network in line with tarombo the. The research method used in this research is a qualitative approach to be able to produce descriptive data regarding the processes of ongoing socio-cultural dynamics. The problem discussed is how the processes of community interaction what happened, and what caused the community to care about the village again page. Have a positive impact on efforts revitalization of these aborigine values as historical sources. The Batak land of Angkola is an ancestral land passed down hereditary as evidence of the existence of a clan in the lifetime of the ancestors who introduced to the next generation. Deep maintaining the Batak culture of Angkola in particular, the parents did formations of the unity of the descendants of the ancestors. This unity will later function strengthening the existing kinship system, becoming a learning platform for the younger generation in knowing the ins and outs of their ancestors and knowing the existing kinship system in Angkola culture.